2014
DOI: 10.1371/journal.pone.0090030
|View full text |Cite
|
Sign up to set email alerts
|

Post-Translational Modifications Modulate Ligand Recognition by the Third PDZ Domain of the MAGUK Protein PSD-95

Abstract: The relative promiscuity of hub proteins such as postsynaptic density protein-95 (PSD-95) can be achieved by alternative splicing, allosteric regulation, and post-translational modifications, the latter of which is the most efficient method of accelerating cellular responses to environmental changes in vivo. Here, a mutational approach was used to determine the impact of phosphorylation and succinimidation post-translational modifications on the binding affinity of the postsynaptic density protein-95/discs lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(61 citation statements)
references
References 40 publications
3
58
0
Order By: Relevance
“…Finally, mutation D332P was designed to emulate the succinimide ring formation at residue Asp332 previously described by us [20]. Another previous study [18] has shown that Asp332 is solvent exposed at the β2–β3 loop, not contacting with any residues of the ligand or of the domain; the cyclation of this position drives to a strong modification of the conformational dynamics of the loop, being this effect the responsible of a net drop in the binding affinity of short linear peptides. These effects can be considered essentially the same when a Pro or a succinimide are present, despite the ring occurs at different positions of the backbone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, mutation D332P was designed to emulate the succinimide ring formation at residue Asp332 previously described by us [20]. Another previous study [18] has shown that Asp332 is solvent exposed at the β2–β3 loop, not contacting with any residues of the ligand or of the domain; the cyclation of this position drives to a strong modification of the conformational dynamics of the loop, being this effect the responsible of a net drop in the binding affinity of short linear peptides. These effects can be considered essentially the same when a Pro or a succinimide are present, despite the ring occurs at different positions of the backbone.…”
Section: Resultsmentioning
confidence: 99%
“…This titration behaviour might be attributed to the protonation equilibriums of some Glu and/or Asp residues, the only ones whose pK a values are within the range of pH 3–4 [23]. This evidence strongly pointed to some of the above mentioned Glu residues, concretely to Glu334 and Glu401, since these are the main responsible for the packing of the extra α3-helix to the domain through salt-bridges with residues Lys355 and Arg399, respectively [18]. The question still unknown is to which extent these electrostatic interactions may also determine the folding/misfolding behaviour of PDZ3, since both salt-bridges would be influenced when Glu residues protonate below pH 3, being the packing of the extra-helix to the whole PDZ3 altered.…”
Section: Introductionmentioning
confidence: 89%
“…In fact, a ∼100-fold stronger binding of the PDZ domain of Pals1 to the Crb tail is achieved upon intra-or inter-molecular interactions between the Src homology 3 (SH3)-and the guanylate kinase (GUK)-domain of Pals1 (Kantardzhieva et al, 2005;Li et al, 2014). Similarly, the affinity of the PDZ domain of the postsynaptic density protein PSD-95 to its ligand is reduced upon phosphorylation of a tyrosine residue in a linker region between the third PDZ domain and the subsequent SH3-domain, thereby weakening the intramolecular interaction between the PDZ and the SH3 domain (Murciano-Calles et al, 2014;Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the heat release when such interactions are formed reflects a favourable enthalpic contribution at neutral pH. The binding entropy counterbalances enthalpy by approximately 15% to 20% and arises from losing conformational freedom because of the structural arrangement of the peptide ligand as a β‐strand in the binding pocket of the PDZ domain . Overall, the net Gibbs energy change is favourable, enthalpically driven, and entropically hindered.…”
Section: Resultsmentioning
confidence: 99%
“…Calorimetric titrations were performed at different temperatures on an isothermal titration calorimetry (ITC) 200 titration microcalorimeter (Microcal Inc) as described elsewhere . Briefly, titrations were made by a series of injections of 2 μL of PSD95‐PDZ2 or HRNTVV solutions into the calorimetric cell containing nNOS‐PDZ or the complex PSD95‐PDZ2/nNOS‐PDZ, respectively.…”
Section: Methodsmentioning
confidence: 99%